URGENSI PERNIKAHAN ANAK DIBAWAH UMUR DITINJAU DARI PERSPEKTIF UNDANG – UNDANG PERKAWINAN - Widiadhana, Vicky; Achmad, Muh Jufri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Marriage is a social pattern that binds both parties, a pair of lovers between a man and a woman in forming a household ark and becoming a family. From the Islamic point of view, a very strong contract is mitsiqan ghalizhan in obeying Allah's commands and carrying it out is worship through certain conditions. In this study, we will examine more deeply about the problems in a child marriage from a legal perspective. The research methods that will be used are qualitative methods, normative juridical approaches, statutory approaches and presentations with descriptive research specifications, use of secondary data, materials, understanding how to interpret data, presenting data based on a theoretical framework, and analyzing using normative qualitative methods. If we look from a legal perspective, underage marriages occur a lot because the marriage law provides tolerance for underage marriages is quite large, by providing the application of an age limit at the age of 16 years in allowing marriage. Of course, in this case, it is very necessary to make an effort to harmonize the various marriage legal systems that apply in Indonesia so that the legislative challenges that arise due to the disparity of legal provisions in the issue of child marriage. in the prevention that can be done from now on is to revise the marriage law and to mature the age in marriage so that these efforts can minimize the prevention of child marriages occurring. The role of the government is very necessary in this regard and is committed to stopping the practice of this underage marriage tradition because in addition to the urgency that is not urgent, it will even add new problems in the development of society such as affecting women's and children's health problems, divorce which will increase due to domestic problems that arise. based on emotions that are still unstable, as well as the safety of mothers and children when they are about to give birth